2017
DOI: 10.24093/awejtls/vol1no1.14
|View full text |Cite
|
Sign up to set email alerts
|

Translating Food Menus from English into Arabic: Linguistic and Cultural Dilemmas

Abstract: Translating food menus is a fundamental communication tool for restaurants and coffee shops to market their products and to inform their costumers about the type, quality and diversity of food and products available for their use. This study aims at investigating some translation strategies used to translate food menus from English into Arabic and the salient linguistic and cultural problems resulted fromthe usage of such inappropriate strategies. This study the focuses the translation strategies used to trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Thus, the most frequently used method of translating Indonesian traditional food names into English is more leaned toward domestication strategy where the appearance of the food is described to assist target readers in recognizing it. Likewise, Al-Rushaidi and Ali (2017) examined food menus translation strategies from English to Arabic in 10 restaurants and coffee shops in Muscat, Sultanate of Oman, and the problems that arose as a result of their use. The study results indicated that frequently employed translation strategies in rendering food menus in the corpus include “borrowing, literal translation, using a superordinate word, amplification, reduction, and using a loan word plus an explanation” in that order, respectively.” The authors also note that the utilization of these procedures resulted in problems including lack of clarity and linguistic ambiguity, leading to misunderstanding of TT.…”
Section: Translation Of Culture-specific Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the most frequently used method of translating Indonesian traditional food names into English is more leaned toward domestication strategy where the appearance of the food is described to assist target readers in recognizing it. Likewise, Al-Rushaidi and Ali (2017) examined food menus translation strategies from English to Arabic in 10 restaurants and coffee shops in Muscat, Sultanate of Oman, and the problems that arose as a result of their use. The study results indicated that frequently employed translation strategies in rendering food menus in the corpus include “borrowing, literal translation, using a superordinate word, amplification, reduction, and using a loan word plus an explanation” in that order, respectively.” The authors also note that the utilization of these procedures resulted in problems including lack of clarity and linguistic ambiguity, leading to misunderstanding of TT.…”
Section: Translation Of Culture-specific Itemsmentioning
confidence: 99%
“…(a) Retention : That is, retaining the phonetic/graphic form of the source language (SL) CSIs, or adapting it to the phonetic structure, spelling, and morphology of the TL. Other scholars refer to this strategy as transliteration (Jiang, 2014; Stoyanova, 2013), transference (Newmark, 1988), and borrowing (Al-Rushaidi & Ali, 2017; Marco, 2019).…”
Section: Translation Of Culture-specific Itemsmentioning
confidence: 99%
“…Reynolds (2016) found that literal translation, transliteration and the addition of an annotation appeared in food translation, but the focus was confined in Taiwanese foods. Al-Rushaidi & Ali (2017) proposed a framework for translating food names. These translation techniques are borrowing, literal translation, using a superordinate word, amplification, reduction, translation by cultural substitution and using a load word plus an explanation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several researchers who ephasize two main functions of menus: to inform and to attract (Al-Rushaidi and Ali, 2017). Customers become informed about a restaurant offer through a menu, while at the same time they are tempted to make a choice.…”
Section: Theoretical Backroundmentioning
confidence: 99%